The genus Xestoleberis (Ostracoda: Xestoleberididae) in the Northern, Northeastern and Eastern regions of the Brazilian continental shelf - Da Luz, Nathália Carvalho; Coimbra, João Carlos (Zootaxa, 2015)
The analysis of 359 samples from three regions of the Brazilian continental shelf (Northern, Northeastern and Eastern) resulted in the recognition of six species of the genus Xestoleberis. One of these species was already described, X. umbonata Whatley et al. 1998, four species are new and herein described, X. inesae sp. nov., X. amazonica sp. nov., X. subtriangularis sp. nov. and X. virilis sp. nov., and one was maintained in open nomenclature, Xestoleberis sp. The species X. inesae sp. nov. is widely distributed in the study area, occurring in all mentioned regions, while X. amazonica sp. nov. is restricted to the Northern region. Xestoleberis subtriangularis sp. nov., X. virilis sp. nov. and Xestoleberis sp. occur in the Northeastern and Eastern regions. Xestoleberis umbonata was recorded in this study only in the southernmost part of the Eastern region.